Gendering mental health : knowledges, identities, and institutions - Davar, Bhargavi V, Ed. Ravindran,T. K. Sundari, Ed
Papers resulting from the proceedings of the 'National Review Workshop on Gender and Mental Health', held at Velha Goa in July 2007.